2017
DOI: 10.1080/09644016.2017.1371919
|View full text |Cite
|
Sign up to set email alerts
|

Deliberative democracy meets democratised science: a deliberative systems approach to global environmental governance

Abstract: The main achievements of the debates on deliberative democracy and democratised science are investigated in order to analyse the reasons, meanings and prospects for a democratisation of global environmental policy. A deliberative systems approach, which emphasises the need to explore how processes in societal spheres interact to shape the deliberative qualities of the system as a whole, is adopted. Although science plays a key role in this, its potential to enhance deliberative capacity has hardly been address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Expertise is never shaped in an organizational vacuum. The construction and maintenance of expertise is important for the legitimacy of expert organizations; for how they are interpreted, evaluated and respected by other actors (Berg and Lidskog 2018;Connelly 2010;Leino and Peltomaa 2012;Turnhout et al 2015). But the construction of expertise is also constitutive of world-making (Jasanoff 2012).…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expertise is never shaped in an organizational vacuum. The construction and maintenance of expertise is important for the legitimacy of expert organizations; for how they are interpreted, evaluated and respected by other actors (Berg and Lidskog 2018;Connelly 2010;Leino and Peltomaa 2012;Turnhout et al 2015). But the construction of expertise is also constitutive of world-making (Jasanoff 2012).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…However, blurring the boundaries between actors and practices -mainly between science, other knowledge systems, and policy -may also have the opposite effect, undermining IPBES's possibility to gain epistemic authority. Political interference in IPBES's scientific practices may restrict and damage the trustworthiness and legitimacy of its knowledge production, preventing it from becoming an epistemic authority (Berg and Lidskog 2018). Thus, there are risks associated with balancing the demands of two competing epistemic logics: the one comprising traditional ideas on the importance of a sovereign and autonomous science delivering knowledge to policy, and the other consisting of newer ideas about the need to include different actors and multiple perspectives in knowledge production in order to produce relevant knowledge.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Kalafatis (2017), in a recent research concerning 287 cities in the US, showed that there is an overlap between economic development and sustainability. To this extent, decision making in environmental policies through a deliberative approach of democracy can be proved effective (Berg & Lidskog, 2017;Payne & Samhat, 2012) leading to Arias-Maldonado's (2000) suggestion that this can be set "between normative sustainability and deliberative democracy".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, deliberation among specialists is often treated as exemplary by deliberative theorists (Moore 2017). However, the degree to which these qualities are transmitted to the rest of the system may vary (Berg and Lidskog 2017). For example, if an instrumentalist rationality dominates within the social sciences, values tend to be neutralized or reductively subsumed under economic values (Smith 2003).…”
Section: Global Environmental Governance and The Deliberative Systemsmentioning
confidence: 99%
“…To overcome this tendency, there are calls for more open, inclusive, and deliberative approaches to decision-making processes regarding global environmental matters (Beck et al 2014). A particular problem is that many of these matters are fundamentally research-dependent, which has led to calls for a Bdemocratized science^in which scientific assessments are more transparent for public evaluation and questioning and according to some proponents more inclusive of stakeholder perspectives (Berg and Lidskog 2017). This paper explores the arguments for expanding deliberation in the IPCC and their potential impact on the deliberative capacity of global environmental governance (GEG).…”
Section: Introductionmentioning
confidence: 99%